Database development and online digital archive retrieval system for Bahagian Arkib dan Muzium (BAM) UiTM / Norashida Sabari - Sabari, Norashida (2011)
Information retrieval is finding material (usually documents) of an unstructured nature (usually text) that satisfies an information need from within large collections (usually stored on computers). Information retrieval has become widely used and becoming the dominant form of information access instead of the traditional database style searching especially to search in the large databases. Bahagian Arkib dan Muzium (BAM) UiTM holds large numbers of data that will be referenced by users. The objectives of this project are to design and develop database for BAM and to develop a document (newspaper cutting) retrieval prototype based on description using Boolean Model. The scope of this project is newspaper cutting containing news on UiTM. In the future, this project needs enhancement to produce better result with implementing advances temming and retrieval techniques.